Mother–Infant and Partner–Infant Emotional Availability at 12 Months of Age: Findings From an Australian Longitudinal Study - Rossen, L.; Mattick, R.; Wilson, J.; Burns, L.; Macdonald, J.; Olsson, C.; Allsop, Steve; Elliott, E.; Jacobs, S.; McCormack, C.; Hutchinson, D. (2018)
Emotional availability (EA) is a focal indicator of parent–infant relationship quality and plays a key role in determining healthy child development, yet factors thought to influence EA have not been examined comprehensively in the postnatal period in both mothers and partners. The aim of this study was to examine the influence of mother–infant and partner–infant bonding, mental ill-health and substance use at 8 weeks postbirth on mother–infant and partner–infant EA at 12 months postbirth, accounting for a range of demographic and postnatal variables. Participants were 191 matched mother–partner–infant triads from a nested sample of an Australian longitudinal pregnancy cohort (The Triple B Pregnancy Cohort). Assessments were conducted at 8 weeks postbirth and at infant age 12 months. Parental EA was coded from dyadic interactions during a 20-min free play observational video recorded at 12 months. Generalized estimating equations (GEE) analysis, accounting for within-dyad clustering, showed older parent age was associated with higher parent–child EA scores (?2 = 6.28, p <.01), while parental tobacco use (?2 = 7.35, p <.01) and depression (?2 = 4.51, p <.05) at 8 weeks postnatal predicted poorer parent–child EA scores at 12 months. These novel findings suggest that it may be particularly important to support young couples and those struggling with symptoms of depression or tobacco use during the postnatal period.